Changes in the Fitness Fatness Index following reduced exertion high-intensity interval training versus moderate-intensity continuous training in physically inactive adults - Leahy, Daniel J.; Dalleck, Lance C.; Ramos, Joyce S. (Frontiers in Sports and Active Living, 2022)
Background Despite the adverse effects of physical inactivity, mMany adults do not reach the recommended exercise participation guidelines, often citing lack of time as a barrier. Reduced exertion high- intensity training (REHIT) is a mode of exercise that takes as few as 10 minutes, andminutes and has been shown to be as effective as other modalities. The Fitness Fatness Index (FFI) is a recently developed index that is used to predict cardiovascular disease (CVD) risk. The aim of this study was to determine the efficacy of a REHIT versus a traditional moderate- intensity continuous training program (MICT) on FFI in physically inactive adults. Methods Thirty-two participants were randomized into one of two 8-week exercise intervention groups: i) REHIT (n=16); ii) MICT (n=16). The REHIT group performed 10 minutes of individualised cycling intervals on 2-4 days of the week. The MICT group were prescribed aerobic exercise at 50-65% of their heart rate reserve (HRR) on 3-5 days of the week. FFI was recorded at baseline and post 8-weeks, with FFI being calculated as cardiorespiratory fitness (CRF) (expressed as metabolic equivalents) divided by waist to height ratio (WtHR). A 1-unit increase in FFI was recognised as a clinically significant change in FFI. Results The REHIT group showed significantly greater (+1.95, ±0.63) improvements in FFI compared to those in the MICT (+0.99, ±0.47) group (between group difference, p<0.001). Furthermore, there was a greater proportion of participants who achieved a clinically significant change in FFI in the REHIT group (12/12, 100%) than in the MICT group (8/15, 53%) (between group difference, p=0.01). Conclusion This study suggests that REHIT may be a more efficacious exercise modality to increase FFI than MICT. This outcome is beneficial as the clinician can prescribe REHIT to physically inactive adults who cite lack of time as a barrier to physical activity participation and achieve significant reductions in CVD risk.